Decision-Making in Suicidal Behavior: The Protective Role of Loss Aversion - Hadlaczky, Gergö; Hökby, Sebastian; Mkrtchian, Anahit; Wasserman, Danuta; Balazs, Judit; Machín, Núria; Sarchiapone, Marco; Sisask, Merike; Carli, Vladimir (Frontiers in Psychiatry, 2018)
Background: Loss aversion is a central and well operationalized trait behavior that describes the tendency for humans to strongly prefer avoiding losses to making equivalent gains. Human decision-making is thus biased towards safer choices. Aim: The aim of this study was to explore the relationship between loss aversion and suicidal behavior in a large cohort of adolescents recruited in 30 schools of seven European countries for a longitudinal study (Current Controlled Trials ISRCTN65120704). We hypothesized that individuals with higher loss aversion would be less likely to attempt suicide. Methods: A mixed monetary gamble task was used to generate loss aversion scores for each participant. Logistic regression was used to estimate the cross-sectional association between loss aversion and life-time suicide attempts in the baseline sample (N = 2158; 156 attempters), and incident attempts were predicted in a four-month prospective model (N = 1763; 75 attempters). Multiple regression was used to estimate the association between loss aversion and suicidal ideation. Results: Loss aversion was a significant predictor of attempted suicide in both the cross-sectional (OR = .79; P = .005) and prospective analysis (OR = .81; P = .040), adjusting for depression, anxiety, stress, and sex. The correlation between pre and post measures of loss aversion was r = .52 (P < .001). Interestingly, although depression, anxiety and stress was associated with suicidal ideation, loss aversion was not (cross-sectional model: P = .092; Prospective model: P = .390). This suggests the concept of loss aversion may be useful in understanding the transition from suicidal thoughts to attempts. Conclusions: This and previous studies suggest that altered decision-making is involved in suicide attempts. In our study we show the involvement of loss aversion in particular, and propose that individuals high in loss aversion are discouraged from carrying out the suicide attempt because of a greater focus on the negative consequences of the decision.